SOC Strategies and Organizational Citizenship Behaviors toward the Benefits of Co-workers: A Multi-Source Study - Müller, Andreas; Weigl, Matthias (Frontiers in Psychology, 2017)
Background: Individuals’ behavioral strategies like selection, optimization, and compensation (SOC) contribute to efficient use of available resources. In the work context, previous studies revealed positive associations between employees’ SOC use and favorable individual outcomes, like engagement and job performance. However, the social implications of self-directed behaviors like SOC that are favorable for the employee but may imply consequences for coworkers have not been investigated yet in an interpersonal work context. Objective: This study aimed to assess associations between employees’ use of SOC behaviors at work and their organizational citizenship behaviors (OCB) towards the benefits of co-workers rated by their peers at work. We further sought to identify age specific associations between SOC use and OCB. Design and Method: A cross-sectional design combining multi-source data was applied in primary school teachers (age range: 23 - 58 years) who frequently teach in dyads. N=114 dyads were finally included. Teachers reported on their SOC strategies at work. Their peer colleagues evaluated teachers’ OCB. Control variables were gender, workload, working hours, and perceived proximity of relationship between the dyads. Results: We observed a positive effect of loss-based selection behaviors on peer-rated OCB. Moreover, there was a significant two-way interaction effect between the use of compensation strategies and age on OCB, such that there was a positive association for older employees and a negative association for younger employees. There were no significant main and age related interaction effects of elective selection, optimization, and of overall SOC strategies on OCB. Conclusion: Our study suggests that high use of loss-based selection and high use of compensation strategies in older employees is positively related with OCB as perceived by their colleagues. However, high use of compensation strategies in younger employees is negatively related with OCB. Our findings contribute to a better understanding of the age-differentiated interpersonal effects of successful ageing strategies in terms of SOC in organizations.